ISSUES OF THE LEGAL FORMALIZATION OF RELATIONS OF HOUSING CONSTRUCTING - Тulenova Гульмира Какеновна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
This article is devoted to the issues of legal formalization of relations of housing constructing by passing the Law of the Republic of Kazakhstan "On the equity in housing construction."